Adrenergic mechanisms of absence status epilepticus - Sitnikova, Evgenia (Frontiers in Neurology, 2023)
Absence status epilepticus is a prolonged, generalized absence seizure that lasts more than half an hour. The mechanisms underlying absence status epilepticus are still not entirely understood. Here I concentrate on alpha2-adrenergic mechanisms of absence status using WAG/Rij rat model. In this model, a prolonged spike-wave activity was associated with a specific behavioral state in transition between sedation («alpha2-wakefulness») resembled absence status in human patients. Pharmacological activation of alpha2-adrenoreceptors may target the locus coeruleus (presynaptic alpha2-adrenoreceptors) and thalamic part of the seizure-generating thalamocortical system (postsynaptic alpha2B-adrenoreceptors). The duration of EEG-behavioral correlates of absence status was not dose-dependent and was predetermined by the intensity of absence seizures at baseline. This model could help scientists to better understand the underlying causes of absence status and develop more effective and personalized treatments for each individual.